CHALLENGES FOR A PERVASIVE INFORMATION ARCHITECTURE: reducing disorientation, increasing legibility and wayfinding - Padua, Mariana Cantisani [UNESP]; Dias, Guilherme Ataide (Univ Federal Campina Grande, 2016)
Due to the Information Science (IS) concerns with information processing processes, we highlight the importance of conducting studies to assist the development of processes and methodologies in hybrid information environments. From this thinking, it is considered that Pervasive Information Architecture proposed by Resmini and Rosati is one of these resources. Thus, this research aimed to assess, through the application of the heuristics proposed by these authors, to the physical and digital information environments of Business Incubation Program (PROINE) of the Federal University of Goias (UFG), analyzing how this instrument contributes to the development of hybrid information environments that maximize the user experience (UX). We correlated methodologies of development technologies and assessment of digital environments and applied the heuristics of Resmini and Rosati enabling to assess both environments through different informational channels. It is noteworthy that the assessment of physical and digital information environments, with the use of support methodologies, allowed to carry out the connections with the heuristics, just by the degree of complexity presented by these principles. This is the key point and main goal achieved, enabling to point out the flaws and make inferences to maximize UX in the use of the assessed informational channels.
Keywords: Hybrid information environments; User Experience; Ubiquitous ecology; Wayfinding